2021
DOI: 10.1002/eat.23506
|View full text |Cite
|
Sign up to set email alerts
|

Bone quality assessed by trabecular bone score in severe anorexia nervosa: A brief report

Abstract: Objective Low bone mineral density (BMD) in anorexia nervosa (AN) leads to increased risk of fractures. Debate exists whether to medicinally treat young patients with AN based on abnormal dual‐energy x‐ray absorptiometry (DXA) scores or to weight restore and reassess when older. Trabecular bone score (TBS), a technology measuring bone quality, is used in conjunction with DXA. This report explores the potential additional value of TBS, in adults with severe AN, to augment the DXA diagnostic information. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Most studies in healthy premenopausal women aged between 20-50 years have described a slow decline ( 26 30 ) in TBS except for a North American study reporting stable TBS values in women aged 30-45 years, followed by a decrease thereafter ( 31 ). Studies assessing TBS in young females with anorexia nervosa have found a positive correlation between TBS and menstrual status ( 32 , 33 ). The high prevalence of abnormal TBS in POI cohorts suggests an accelerated loss of microarchitectural integrity due to prolonged hypoestrogenism.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies in healthy premenopausal women aged between 20-50 years have described a slow decline ( 26 30 ) in TBS except for a North American study reporting stable TBS values in women aged 30-45 years, followed by a decrease thereafter ( 31 ). Studies assessing TBS in young females with anorexia nervosa have found a positive correlation between TBS and menstrual status ( 32 , 33 ). The high prevalence of abnormal TBS in POI cohorts suggests an accelerated loss of microarchitectural integrity due to prolonged hypoestrogenism.…”
Section: Discussionmentioning
confidence: 99%
“…TBS, determined from lumbar spine DXA images, reflects qualitative aspects of the skeletal structure, providing an indirect index of trabecular microarchitecture that is partially independent of, but complementary to, BMD [ 64 ]. Although its use in the extreme ends of BMI is questioned due to the possible source of bias of too little or too much adipose tissue interposed between the spine and the X-ray, TBS has become a reference tool for skeletal assessment, and several studies support its reliability and reproducibility in clinical practice, both in underweight [ 65 ] and obese populations [ 66 , 67 ]. We found that most of the patients with obesity had the lowest value of TBS, confirming that the worse the metabolic state, the greater the suffering of the trabecular bone [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…( 59 ) Reduced trabecular bone score (TBS), identified in 13% of women in a subgroup with AN and lower BMI than the rest of the cohort, suggests worsened bone quality in those with lower weight. ( 60 ) Improvement of BMD in these women are challenging, and rely on weight restoration ( 61 , 62 , 63 ) and resumption of menses. ( 62 , 63 ) A cross‐sectional study of women revealed that moderate‐intensity exercise while unwell with active AN worsens BMD.…”
Section: Methodsmentioning
confidence: 99%